Analisis Teori Ekspresi Cinta Remaja Sebagai Pencegahan Perilaku Seksual Berisiko dengan Menggunakan Strategi Penekanan Ekspresif - Agrery Ayu Nadiarenita; Nur Hidayah (Universitas Mathla'ul Anwar Banten, 2018)
ANALYSIS OF EXPRESSION THEORY OF ADOLESCENT LOVE AS PREVENTION OF SEXUAL BEHAVIOR BY USING EXPRESSIVE SUPPRESSION STRATEGY. Love is a form of positive emotion expressed differently by each individual. As a positive emotion, love should be interpreted as an element of emotion in which there is mutual respect, trust and respect for each other in order to maintain the relationship of sexual attraction that cause feelings of pleasure. Expression of love is now interpreted as a negative emotion in which the urge of passions that play a big role in a relationship. Sexual impacts will affect teenagers when the relationship is sustained, including increased rates of pregnancy out of wedlock, dropping out of school, and increased HIV/AIDS transmission. Based on a survey conducted by several agencies stating that Indonesia is an emergency against teenage sexual behavior. Therefore, this study was conducted with the aim to find solutions to adolescent problems in order to prevent excessive love expression. Expressive suppression strategy as a response modulation strategy is expected to be a solution for teenagers. Use of this strategy by applying the stages in emotional regulation. The effectiveness of this technique to prevent excessive love expression needs to be proven in further research so that it can be used to assist school counselors in dealing with students.